PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII A SMP NEGERI 2 KUTA TAHUN PELAJARAN 2017/2018 - Ni Ketut Dharmawati Geria Putri (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
This study aims to: improve science learning outcomes through the application of problem posing learning models in Class VIII Semester 2017/2018 Academic Year. This research is a classroom action research, which took place in 2 cycles. The research subjects were students of class VIII. Data collection techniques using assignments and tests. Data were analyzed using descriptive analysis in percentage and qualitative data analysis with reference to the Minimum Mastery Criterion (KKM = 76) and Classical Mastery (KK = 85%) for science subjects in VIII grade at SMP Negeri 2 Kuta in the academic year 2017/2018. The results showed an increase in science learning outcomes, namely: the average value of learning outcomes and classical completeness before action were 71.1 and 62%. In the first cycle the average learning outcomes in knowledge competence was 76.4 with a classical completeness of 68%. The average student learning outcomes on skills commentary was 77.5 with a classical completeness of 62%. In cycle II the science learning outcomes in knowledge competence were 82.6 with a classical accuracy of 94%, the learning outcomes in the skills competence were 86.5 with a classical completeness of 100%. Based on these results it can be concluded that the application of the problem posing learning model can improve the learning outcomes of students of class VIII A of SMP Negeri 2 Kuta in the even semester of the academic year 2017/2018.